High Frequency Applications of Metamaterials and Metasurfaces - Bhattacharya S.; Saha C.; Siddiquiand J.Y. (My University, 2025)
In this article, various applications of metamaterials and metasurfaces have been briefly mentioned. © 2019 IEEE.